The magic school bus : gets programmed a book about computers - Cole, Joanna (New York : Scholastic Inc, 1999)
Mr. Ruhle, the school principal, has just gotten a super-duper computer. And Carlo's brother Mickey programs it to do all of the class's chores.
Keywords: Computer-Fiction